COMMUNITY PARTICIPATION IN SOLID WASTE MANAGEMENT: THE CASE OF KURUNAGALA MUNICIPAL COUNCIL IN THE NORTH WESTERN PROVINCE OF SRI LANKA - Pinnawala, Mallika (Malaysian Journal of Science, 2016)
ABSTRACT Solid Waste Management (SWM) refers to the supervising and handling of SW from its generation to disposal. As a developing country, in Sri Lanka, Solid Waste has become one of the growing national problems, especially in urban areas where there is no proper mechanism to manage it. Citizens always assume that SWM is a responsibility of Local Authorities (LAs). But waste is generated from human activities and citizens also have a responsibility in managing them. Therefore community participation is a crucial factor for sustainable SWM process in a country. There are two objectives of this study, namely, to examine community strategies in managing SW at the household level and to understand community cooperation with LAs in managing it in community level . The study was conducted in one administrative zone in Kurunagala Municipal Council in the North Western Province of Sri Lanka covering 160 households selected through simple random sampling method. A Questionnaire survey was used to collect data to understand community participation in SWM at the household level. In-depth interviews with Municipal Council (MC) officers and sanitary labours who are involved in SWM of the Municipal Council were conducted to gather data on community cooperation with LA in Managing SW. The study revealed around 90 % of residents use one strategy of 3R concept in managing SW. Reduced solid waste through reuse is a popular and common strategy used by the respondents in the area. The percentage is around 88%. Respondents also prefer recycling and separation to manage their household solid waste but the facilities provided by the LA are not sufficient. Some people are not aware of the problem of solid waste and also about managing strategies of solid waste. According to LA officers, community cooperation for solid waste management is at average level. Keywords : Sri Lanka ,Solid Waste Management, Community Participation, Local Authorities Municipal Council, 3R concept,